Современный преподаватель высшей школы и системы дополнительного профессионального образования: разнообразие его профессиональных компетенций в России и за рубежом - Даутова, Ольга Борисовна; Крылова, Ольга Николаевна (International Dialogues on Education Journal, 2016)
The article deals with high-school teachers (university teachers) and supplementary vocational education (SVE) teachers. The authors cover the requirements for the quality of preparation for these positions under the conditions of applying the competence approach. The teachers’ professional competence as it exists in Russia and abroad is analysed; various scientific schools’ approaches and predictions of the groups’ competence are presented. The study of the requirements for the occupational preparation of high-school and SVE teachers by students, teachers themselves, and representatives of the authorities from different countries has shown that they all single out such professional characteristics as personal responsibility, communication skills, subject knowledge, the ability to manage educational processes, intellect, professional interests, etc. In the article the authors’ approach to identifying the competency formation levels is presented, such as informational, operational, personal and reflective levels; as well the criteria for the estimation of the given competencies are stated. The estimation of the criteria is based on such characteristics as depth and width. The authors point out that today there is no unified approach to the formation of the set of competencies of high-school and SVE teachers and to the determination of their levels. Nevertheless, work in this direction is actively carried out in various scientific schools.